Multiple Cerebral Aneurysms in Factor VII Deficiency - Schilling, Andreas M.; Heidenreich, Jens O.; Oldenburg, Anja C.; Pietilä, Terttu; Stendel, Rüdiger; Wolf, Karl-Jürgen (American Journal of Neuroradiology, 2004)
Summary: A rare case of multiple cerebral aneurysms and factor VII deficiency is presented. The authors hypothesize a possible combined genetic defect similar to that of other conditions with clotting disorders. Different treatment options are discussed for factor VII deficiency in particular and multiple cerebral aneurysms in general. The authors advise treatment of all detected aneurysms in case of a subarachnoid hemorrhage rather than only treatment of the ruptured aneurysms in order to immediately start the so-called triple-H therapy.